Precariado em questão: uma investigação a partir de seus teóricos - Fernandes, Vinicius Tomaz (2019)
The structural crisis of the capital has brought ongoing changes in the workforce enviroment, starting mainly in the 1970s decade, and it has left a rather strong imprint on the being of the working class. Since then, there is a vigorous effort by theoretical sociology in reinterpreting this reality either by denying, reafirming or in elaborating new categories. It’s in this scenario which this thesis is based on, and it has the objective of doing a general examination of the theoretical-methodological foundations of the “precariat” concept, and if there is explanatory potential to correctly comprehend social classes in the modern days. Therefore, we seek comprehending the precarity of the workforce as a condition of the devolopment of the capitalist mode of production and the precariousness throughout the historical process. Then, we did a critical review in what we call “theories of precariat” based on the work of Guy Standing, responsible for the propagation of the concept, as well as the work of brazilian sociologists Giovanni Alves and Ruy Braga, whom, in their own manner, have reworked the concept in new theoretical basis. We bring a lot of flak to the precariat, from those that rebut the concept in it’s entirety, to those that although deny it’s utilization in the analysis of class structure, recognize it’s political role. And finally, we came to the conclusion that the concept is justified when circumscribed to a political field, given the rhetoric and the mobilization, we argue that the concept is incapable of composing an analysis of classes in this conjunction.